Penanaman Nilai-Nilai Islam dalam Pembentukan Kepribadian Muslim Ummah - Siti Zailiah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
The formation of Muslim personality as an ummah is a person who is ingrained in the ukhuwah Islamiyah, so that they always do good and prevent evil by adhering to the Qur'an and Sunnah of the Prophet. In the Qur'an there is a change in the form of the word ummah, which shows ummatan wahidah, which shows a unity that is not divided because of differences in ethnicity, race and culture. Ummatan wasathan is a moderate ummah, khoiru ummah is a superior ummah, baldatun thayyibatun is a prosperous country, ummatan muqtashidah which describes an ummah that is not extravagant. The research method is a library research. There are four characteristics of library research, namely: 1) research deals directly with text (manuscripts) or numerical data and not with direct knowledge from the field or eye witnesses in the form of events, people or other objects, 2) library data is ready to use (ready mode), 3) library data are generally secondary sources and 4) library data is not limited by space and time because it is already "dead" data stored in written records. So in this study using library research. The personal application of Muslims as an ummah is to shape the personality of Muslim individuals so that they become human beings who are submissive and obedient to Allah, prioritizing His interests over other interests in the sense that they do not wish to become human beings who are negligent in remembering Allah SWT. So when a child lives in a religious family, of course, after joining the community, he is not easily influenced by the western lifestyle, because the values of Islamic teachings are instilled, which are guided by the Al-Qur'an and the Sunnah of Rasulullah SAW. Therefore, the Prophet recommended that in choosing a mate, Islam teaches to be selective because it will give birth to generations who are expected to become caliphs on earth, as servants who are submissive and obedient to the commands of Allah SWT.